Chronic Non-bacterial Osteomyelitis in Childhood – a Comprehensive Review - Morbach, Henner; Girschick, Hermann J. (Current Rheumatology Reviews, 2013)
The clinical picture of childhood chronic recurrent multifocal osteomyelitis (CRMO) is characterized by an aseptic chronic osteomyelitis, most often affecting the metaphyses of the long bones. Skin inflammation (palmoplantar pustulosis, psoriatic lesions, acne) and inflammatory bowel disease may be associated with CRMO and therefore subsume this disease into the entity of SAPHO syndrome. Deregulated cytokine/chemokine expression in myeloid cells seems to drive chronic inflammation of the disease. NSAIDs may reduce pain, but additional second-line treatments (DMARDs, biologicals) are needed to treat persisting or progressing inflammation in a significant number of patients. The use of bisphosphonates may be a promising option in treating NSAID-refractory osteomyelitis in CRMO.
Keywords: chronic recurrent multifocal osteomyelitis